A Comparative Study on Acute Pain Management at Emergency Room in Traumatic Hip Fracture Patients Using Ultrasound Guided Fascia Iliaca Block Versus Standard Pain Relief Care- A Randomized Clinical Study - muralidhasan, Thanigaivasan; Kannan. S, Kannan. S; S. Bhuvana, S. Bhuvana; Udhayanan, Udhayanan (Journal of Neonatal Surgery, 2025)
On arrival pain relief helps the patient to get mobilized easily for the early radiological examinations and undergo bedside procedures. As the first stage of care and preoperative optimization of hip fracture patients, prompt deployment of multimodal analgesic protocols in the emergency departments is crucial. In this setting, initial interventional analgesic approaches have been shown to reduce procedural sedation and analgesia (PSA), opioid consumption, as well as the associated delirium and opioid- related side effects which is being routinely followed in many accident and trauma care centres. It has its own consequences, like compromised hemodynamic and airway. Such patients require close monitoring before and after the procedure for several hours, before being transferred or discharged from the emergency department (ED). Ultrasound-guided peripheral nerve block is an effective alternative that uses minimal quantities of local anaesthetic and requires minimal monitoring.